المُنَسَّى في القرآن الكريم " المبحث المَنْسِيّ في مباحث علوم القرآن - سكيو, Farida (جامعة الوادي - University of Eloued, 2021)
وردت في كتب السنة أحاديث تدل على رفع بعض آي القرآن الكريم وسوره، وذهابها تلاوة دون الحكم ،أو ذهابها ورفعها تلاوة وحكما معا ، واعتبر العلماء ذلك من قبيل النسخ،ولكنه في حقيقته لا يشبه النسخ في تعريفه وشروطه وإنما هو القرآن المُنَسَّى ( بضم الميم وفتح النون والسين مع تشديد السين،وألف مقصورة بعدها ) الذي أشار إليه قول الله تعالى: (أَوْ نُنْسِهَا) في قوله:( مَا نَنْسَخْ مِنْ آيَةٍ أَوْ نُنْسِهَا ) ،وقد تناولتْ كتب علوم القرآن قديما وحديثا ، موضوع النسخ في القرآن الكريم وهو المتعلق بالشطر الأول من الآية ( مَا نَنْسَخْ مِنْ آيَةٍ ) لكنها أهملت ما نُسِيَ من القرآن الكريم الذي تحدث عنه الشطر المتبقي من الآية وهو قول الله تعالى: ( أَوْ نُنْسِهَا ) ، وجعلوه من المنسوخ ،فالتبس به وأشكلت على الباحثين كثيرا من الروايات المتعلقة به ،حتى ذهب بعضهم إلى إنكار النسخ لما وجدوه من اضطراب فيه. وقد نبه الصحابة رضي الله عنهم فيما رُوي عنهم ، إلى رفع بعض القرآن ومحوه من القلوب ، وعدم اعتباره قرآنا يتلى رغم بقاء بعضه ، ولذلك كان هذا البحث محاولة لرفع الاضطراب الذي يمكن أن يثار حول أنواع النسخ ، ببيان المراد من المًنَسَّى ، وبيان أقسامه وأدلته وعلاقته بالنسخ، وأسميته " المُنَسَّى في القرآن الكريم ـ المبحث المَنْسِي من مباحث علوم القرآن ـ Some Ahadith ( prophet sayings) are occured in sunnah's books which indicates : the exalting of some verses and chapters from the holy quran and their recitation going without their islamic rulings or both ; recitation and islamic ruling's exalting . Scholars are considered it such an abrogation but actually it doesn't look like abrogation (En_naskh) in its definition or conditions but its the part of quran which forgotted by Allah's wisdom (Al_mounassa) . Quran's sciences books are adressed in past and present the abrogation in the holy quran (Al_naskh) which relates to the first part from the verse (ما ننسخ من آية ) , but it neglects the rest of the verse (أو ننسها) which is forgotten , and considered it from the abrogated quran (Al_mansoukh) which makes both of them becames confused ,even scholars faced o lot of problems on the abrogation's narrations which promoted some of them to denial it becouse of the troubles founded on it . Companians noticed intheir narrations to the raising of some of the holy quran , and erasing it from hearts , and not being considered as a quran although some of it remains . This article was a try to lift the troubles which maybe being raised about the abrogation's types with showing watswanted from the forgotted part of quran and indicating its relation with the abrogation . I named it [ the forgotten part of the quran ] (Al_mounassah fi el quran ) _the forgotten chapter from the quran's sciences' chapters _
مقال
Keywords: الـمُـنَسَّى في القرآن ؛ مباحث علوم القرآن؛ المبحث الـمَـنْسِيّ؛ النسخ ؛ نسخ التلاوة.